A fully bio-based benzoxazine as latent catalyst for bisphenol A/aniline-based benzoxazine. (September 2019) - Ren, Shitong; Miao, Xiangyan; Zhao, Weibo; Zhang, Shaoyue; Wang, Wei
Graphical abstract: Abstract: Lowering the curing temperature has always been one of the research focuses of polybenzoxazine. In this work, a fully bio-based phenolic hydrogen containing benzoxazines (PF) with high polymerization activity was conveniently synthesized from pyrogallol, furfurylamine and paraformaldehyde through a modified route. The structure of PF was confirmed by FT-IR and NMR. PF was used as a latent catalyst for the traditional bisphenol A/aniline-based benzoxazine (BA), and thermosets with different PF contents were prepared. The influence of PF on the polymerization temperature, thermal and mechanical properties, thermal stability and flame retardancy were symmetrically studied through DSC, DMA and TGA, respectively. The results showed that both the onset exothermic temperature ( T onset ) and exothermic peak temperature ( T p ) decreased obviously with the increase of PF content. The glass transition temperature ( T g ) and crosslinking densities of the thermosets positively correlated with the PF content, while the storage modulus showed a maximum when PF content was 2.5 wt%. The thermal degradation temperatures and char yields of the thermosets were also improved continuously as PF content increased. In brief, by adding a small amount of PF (≤10 wt%), the overall performance of BA resin could be effectively modified.